2021
DOI: 10.51544/jalm.v6i1.1894
|View full text |Cite
|
Sign up to set email alerts
|

KONTAMINASI Salmonella sp. PADA SOP BUAH YANG DIJUAL DI JALAN DR. MANSYUR KELURAHAN PADANG BULAN KOTA MEDAN

Abstract: Sop buah merupakan salah satu jenis minuman yang terdiri dari campuran berbagai macam buah, sirup, susu, air dan es. Ada beberapa faktor yang dapat menyebabkan perubahan manfaat sop buah menjadi sumber penyakit bagi tubuh meliputi: air sebagai bahan sop buah dan air yang digunakan untuk mencuci mangkok dan sendok dapat menjadi bahan kontaminasi penyebab penyakit seperti Salmonella sp. Tujuan penelitian ini adalah untuk mengidentifikasi Salmonella pada sop buah yang dijual di Jalan Dr. Mansyur Kelurahan Padang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Sources of pathogenic bacteria contamination can come from workers, equipment, insects, and environmental factors such as air and water in contact with the product. This research was supported by [17] who stated that contamination of fresh beef by spoilage bacteria can be through dust, water, air, and humans. The test results of pathogenic bacteria contamination in fresh meat and bekamal is shown in Table 1.…”
Section: Resultsmentioning
confidence: 73%
“…Sources of pathogenic bacteria contamination can come from workers, equipment, insects, and environmental factors such as air and water in contact with the product. This research was supported by [17] who stated that contamination of fresh beef by spoilage bacteria can be through dust, water, air, and humans. The test results of pathogenic bacteria contamination in fresh meat and bekamal is shown in Table 1.…”
Section: Resultsmentioning
confidence: 73%
“…Salmonellosis is characterized by acute symptoms of fever, abdominal pain, diarrhea, sometimes vomiting. Salmonellosis is a term that indicates infection by Salmonella sp germs [3]. The previous research also reported that some fresh vegetable salad samples at traditional markets and street stalls contain Salmonella [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic identification showed that those were closely related to the species Klebsiella pneumoniae, Bacillus subtilis, Pseudomonas stutzeri, and Bacillus sp. (Rizqoh et al 2016). The ethyl acetate fraction of Rendeu contains flavonoids, saponins, tannins, steroids and triterpenoids, as well as phenols (Maulani et al 2017).…”
Section: Introductionmentioning
confidence: 99%